2020
DOI: 10.1096/fj.202000201r
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia‐reperfusion injury of brain induces endothelial‐mesenchymal transition and vascular fibrosis via activating let‐7i/TGF‐βR1 double‐negative feedback loop

Abstract: Let-7i modulates the physical function and inflammation in endothelial cells (ECs).However, whether the let-7i of ECs involves in brain vasculature and ischemic stroke is unknown. Using inducible Cadherin5-Cre lineage-tracking mice, a loxp-RNAsponge conditional knockdown of let-7 in ECs-induced increase of transforming growth factor-β receptor type 1 (TGF-βR1), endothelial-mesenchymal transition (endMT), vascular fibrosis, and opening of the brain-blood barrier (BBB). By this lineage-tracking mice, we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…let-7i expression is somewhat correlated with the impact of reperfusion injury, and its expression is strongly correlated with preservation and recovery of post-stroke function [26]. This may be due to its role in regulating leukocyte attachment and recruitment to the brain endothelium [27], along with its importance in other mechanisms of endothelial selfrepair [28]. let-7c is critical for mediating both the recruitment of immune cells to ischemic tissue [19] as well as the activation of multiple repair pathways within the endothelium [20].…”
Section: The Let-7 Family and Inflammationmentioning
confidence: 99%
“…let-7i expression is somewhat correlated with the impact of reperfusion injury, and its expression is strongly correlated with preservation and recovery of post-stroke function [26]. This may be due to its role in regulating leukocyte attachment and recruitment to the brain endothelium [27], along with its importance in other mechanisms of endothelial selfrepair [28]. let-7c is critical for mediating both the recruitment of immune cells to ischemic tissue [19] as well as the activation of multiple repair pathways within the endothelium [20].…”
Section: The Let-7 Family and Inflammationmentioning
confidence: 99%
“…EndMT is a key mechanism in generating diverse cells with migratory and invasive abilities, which involves numerous physiological and pathological events. [56][57][58] After cardiac cushion formation, endothelial cells of outflow tract under transformation into mesenchymal cells via EndMT to generate the primordia of the valves and membranous septa. 58,59 During development, most fibroblasts in the interventricular septum are originated from endocardial cells via EndMT.…”
Section: Endmt In Cardiovascular Diseasesmentioning
confidence: 99%
“…Previous studies found that the traits of endothelial cells were altered following injury (i.e., transdifferentiating into fibroblastic-like cells via endothelial-mesenchymal transition (endMT)) [ 45 ]. Although a recent study showed that reperfusion after ischemia causes endMT in brain [ 46 ], our previous study using genetic mapping for the endothelial cell marker VE-cadherin showed that endothelial cells within and around ischemic areas did not transform into fibroblastic-like cells, and that they maintained expression of the endothelial marker during the acute phase [ 13 ]. In that study, we also found that expression of VE-cadherin was increased at both the promoter and protein level within ischemic areas.…”
Section: Findings After Early Reperfusion Under Lethal Ischemia Inmentioning
confidence: 99%